2014
DOI: 10.1007/s00774-014-0594-6
|View full text |Cite
|
Sign up to set email alerts
|

Daily physical activity in low-risk extremely low birth weight preterm infants: positive impact on bone mineral density and anthropometric measurements

Abstract: The aim of this study was to evaluate the changes in bone mineral density and anthropometric indices of extremely low birth weight (ELBW) preterm infants undergoing daily physical activity. Twenty-eight low-risk ELBW preterm infants (intervention group = 14, control group = 14) with a birth weight of under 1000 g and gestational age of 26-32 weeks were recruited. Preterm infants in the control group were provided with standard nursing care, whereas those in the intervention group received a daily physical acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 31 publications
0
17
1
1
Order By: Relevance
“…Post hoc, sub-group analysis was done to compare infants in each strata with GA 27 0/7 to 32 6/7 and 33 0/7 to 34 6/7 respectively, and also by their intrauterine growth Our findings are in contrast to the literature which shows either attenuation of decline in bone SOS [12,13] or increase in bone SOS with physical activity [14,15]. Our results are similar to the study by Moyer-Mileur, et al, [16] in which no difference was found in bone mineral content or bone area at 12 months of corrected age when compared between exercise and control group.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…Post hoc, sub-group analysis was done to compare infants in each strata with GA 27 0/7 to 32 6/7 and 33 0/7 to 34 6/7 respectively, and also by their intrauterine growth Our findings are in contrast to the literature which shows either attenuation of decline in bone SOS [12,13] or increase in bone SOS with physical activity [14,15]. Our results are similar to the study by Moyer-Mileur, et al, [16] in which no difference was found in bone mineral content or bone area at 12 months of corrected age when compared between exercise and control group.…”
Section: Discussioncontrasting
confidence: 68%
“…The baseline values of bone SOS in their study were significantly higher in control group as compared to intervention group and no adjustment was done during statistical analysis. Another study from Turkey [15] found a slightly higher bone SOS in exercise group in ELBW infants but the sample size was small and confidence intervals were wide. Our study population had a larger sample size, included small for gestational age infants and was racially and ethnically very different.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It was noted to enhance the body weight, bone mineralization and osteogenesis. Some studies have shown that the exercise could attenuate the postnatal reduction in bone speed of sound (47)(48)(49)(50)(51). It is interesting that nutrition plays a dual role in MBD, both therapeutic and preventive.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Again, these severely ill infants with prolonged mechanical ventilation and possible sedation lay immobile for long periods of time so that the antigravitational movements that could promote bone matrix deposition are absent. Erdem et al evaluated the changes in bone mineral density and anthropometric indices of ELBW preterm infants undergoing daily physical activity (Erdem et al 2015). In this small randomized controlled trial, patients who underwent daily physical activity showed increasing tibial SOS values after birth, while patients treated with standard care showed decreasing tibial SOS values.…”
Section: Metabolic Bone Disease In Preterm Infantsmentioning
confidence: 99%